Ablasi Ventrikel Takikardia Outflow Tract - Erika Maharani; Yoga Yuniadi (The Indonesian Heart Association, 2012)
Tachycardia of right ventricular outflow tract (RVOT) is the most common cause of nonischemic ventricular tachycardia (VT). It is commonly due to idiopathic RVOT tachycardia. Idiopathic RVOT tachycardia is a nonfamilial and benign condition that occurs in young individuals without structural heart disease. Radiofrequency ablation has a high successful rate to eliminate this arrhythmia. Non contact mapping can be very helpful in patient with nonsustained tachycardias. We report the case of a 55-year-old man who presented with non sustained ventricular tachycardia and was successfully underwent radiofrequency ablation using non contact mapping.